2007
DOI: 10.1002/ajim.20517
|View full text |Cite
|
Sign up to set email alerts
|

Occupational heat illness in Washington State, 1995–2005

Abstract: HRI cases occur in employed populations. HRI rates vary by industry and are comparable to those previously published for the mining industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
98
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 13 publications
11
98
2
Order By: Relevance
“…Had only lost time claims been included, the rate would have been a tenth of that observed in Ontario. 9 Comparing trends of heat illness by industrial sector reveals similar patterns in Washington State as were noted in Ontario, the exception being the state's Manufacturing sector, which had proportionally fewer heat claims relative to all claims. 9 These differences are likely attributable to regional differences in climate, occupational demographics, prevention programming and claim administration, and reinforce the need for region-specific understanding of occupational heat illness.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Had only lost time claims been included, the rate would have been a tenth of that observed in Ontario. 9 Comparing trends of heat illness by industrial sector reveals similar patterns in Washington State as were noted in Ontario, the exception being the state's Manufacturing sector, which had proportionally fewer heat claims relative to all claims. 9 These differences are likely attributable to regional differences in climate, occupational demographics, prevention programming and claim administration, and reinforce the need for region-specific understanding of occupational heat illness.…”
Section: Discussionmentioning
confidence: 82%
“…Drawing on studies of heat illness in the US states of Washington and California, we might estimate that between 45-90% of cases with less severe heat illness that do not require time off work do not get reported in lost time compensation data. 9,25 While some of this burden was likely captured in the ED encounters, cases treated in primary care or workplace settings were excluded from this surveillance study of the Ontario labour force.…”
Section: Discussionmentioning
confidence: 99%
“…During the first week of an unaccustomed heat exposure, work performance is most affected and the threat of heat illness is greatest (Taylor, 2006). Additionally, it has been reported that 14% of heat-related illness occurred within the first week for inexperience construction workers (Bonauto et al, 2007). Therefore, it is suggested that special attention and arrangement should be given to less acclimatized rebar workers.…”
Section: Discussionmentioning
confidence: 99%
“…Workers who are more acclimatize to the heat stress and high workload have less risk for heat related illness (Bonauto et al, 2007). Heat acclimatization is a series of physiological changes or accommodations of the body in response to repeated heat stress exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Bonauto et al 6 Additionally, the heat related illness claim rates in North America were highest in the third quarter of each year due to increased exposure to hot environments. The higher outdoor temperatures from May to September accounted for 95% of the total heat related illness claims during these months.…”
Section: Incidence Of Heat Illnessmentioning
confidence: 99%